Sifat Fisikokimia Bubuk Dadih yang Diperoleh dari Fermentasi Tradisional Susu Kerbau dan Mocaf melalui Proses Spray-Drying - Iza Ayu Saufani; Sri Anna Marliyati; Eny Palupi; Ekowati Handharyani (Amerta Nutrition, 2026)
Background: Dadih, a fermented buffalo milk product rich in probiotics, can be combined with modified cassava flour (mocaf) as a prebiotic source to enhance the nutritional value of the functional product. The innovation of dadih into powders can extend its shelf life, meanwhile studies on the addition of mocaf as a filler in the drying process are limited. Objectives: To investigate the physical and chemical properties of spray-dried dadih powders with addition of mocaf. Methods: The study employed a quasi-experimental design with two treatment groups: control (50% maltodextrine) and treatment (50% mocaf). The experiment was  conducted in duplicates by measuring physical properties of mocaf-added dadih powder, including yield, bulk density, color  (colorimeter), and particle morphology  (digital microscope). Chemical properties were analyzed from proximate analysis, including moisture, ash, protein, fat, and carbohydrate content. Data were analyzed using an independent sample t-test. Results: Mocaf addition in spray-dried dadih significantly affected the yield and color, but, did not significantly affect the bulk density and particle morphology. The chemical properties of the mocaf-added dadih powder obtained  moisture content of 4.71-5.91%, ash content of 1.84-2.33%, protein content of 5.48-6.08%, fat content of 1.84-2.33%, and carbohydrate content of 84.56-84.94%. The yield was obtained at 10.79-11.37% with bulk density of  0.38-0.42 g/ml. The dadih powder had  yellowish white color, with a value of 8.64-8.61, showing a significant color difference compared to dadih powder using maltodextrine. Conclusions: Mocaf can be used as an alternative filler material in the production of dadih powder with good physicochemical properties.